Can Intraprostatic Injection of OnabotulinumtoxinA be Benefi cial to Treat Premature Ejaculation? Results of a Prospective Study - Taha A. Abdel-Meguid,; Ahmed J. Alsayyad,; Abdulmalik M. Tayib,; Hasan M. Farsi,; Hisham A. Mosli,; Moataz Sait,; Ahmed Abdelsalam, (Journal of King Abdulaziz University: Medical Sciences, 2023)
We prospectively evaluated efficacy and adverse effects of intraprostatic injections of onabotulinumtoxinA to treat premature ejaculation. Twenty-four men ?19 years-old with premature ejaculation for ? 6 months and intravaginal ejaculation latency time ? 2 minutes underwent transurethral intraprostatic injections of onabotulinumtoxinA (100 U). Primary endpoint was change of intravaginal ejaculation latency time at 3-months. Secondary endpoints included changes in premature ejaculation profile and patient-reported global impression of change (PGI). Mean baseline ejaculation latency time has significantly increased at 1-, 3- and 6-months, respectively. In premature ejaculation profile “perceived control over ejaculation”, significant improvement was reported at 3-months, while non-significant changes were reported at 1- and 6-months. Patients reported non-significant changes of “personal distress related to ejaculation” and “interpersonal difficulty related to ejaculation”. Only 8.3%, 12.5% and 12.5% of men reported “better” at 1-, 3- and 6-months, respectively, while all other patients reported “no change” or “slightly better” in patient-reported global impression of change. No serious adverse effects were observed. Improvements of intravaginal ejaculation latency time were not clinically meaningful, as most men reported “no change” or “slightly better” in patient-reported global impression of change. These marginal improvements did not support using onabotulinumtoxinA intraprostatic injections to remedy premature ejaculation.